Analisis Kesuksesan Sistem Informasi Manajemen Puskesmas pada Pengelolaan Obat di Puskesmas Kabupaten Batang - Rizza Fauziyah; Satibi Satibi; Eko Nugroho (Faculty of Pharmacy, Universitas Gadjah Mada)
Every Public Health Center in all regions of Batang Regency has implemented a Public Health Center Management Information Systems (SIMPUS) in drug management since 2010 to accelerate access to the drug data, accelerate and improve the accuracy of prescription services, as well as provide accurate and timely information to support the planning, supply, and distribution processes. This study aims to analyze the level of success in the use of information management systems for drug management in the Batang District public health center in terms of user perceptions. This research is a descriptive quantitative analytic. The data from 29 respondents were collected using a questionnaire survey developed from the updated Delone and McLean success model. The quantitative analysis of the questionnaire uses a